Examining the relationship between genetic polymorphisms (BDKRB2, GNB3, HIF1A, MCT1, NOS3) and endurance athlete status - Ipekoglu, G.; Apaydin, N.; Çetin, T.; Eren, A. N.; Topçu, P.; Yücelsoy, B.; Civelek, G.; Sakar, M. (European Journal of Applied Physiology, 2024)
Purpose Genetic factors are important in terms of athletic performance. Recent studies to determine the relationship between the genes that lead to physiological responses have attracted attention. In this respect, this meta-analysis study was designed to examine the relationship between genetic polymorphism (BDKRB2 rs5810761, GNB3 rs5443, HIF1A rs11549565, MCT1 rs1049434, NOS3 rs2070744) and endurance athlete`s status.